Amp-TB2: An Updated Model for Calcic Amphibole Thermobarometry - Ridolfi, Filippo (Minerals (Basel), 2021)
Amphibole (Amp) plays a crucial role in the study of several earth and planetary processes. One of its most common applications is in thermobarometry, especially for volcanic-magmatic systems. However, many thermobarometers require the input of melt composition, which is not always available in volcanic products (e.g., partially crystallized melts or devitrified glasses), or show rather high errors for characterizing the depth of magma chambers. In this work, a new version of amphibole thermobarometry based on the selection of recently published high-quality experimental data is reported. It is valid for Mg-rich calcic amphiboles in magmatic equilibrium with calc-alkaline or alkaline melts across a wide P-T range (up to 2200 MPa and 1130 °C) and presents the advantage of being a single-phase model with relatively low errors (P ±12%, T ±22 °C, logfO2 ±0.3, H2O in the melt ±14%). A user-friendly spreadsheet (Amp-TB2.xlsx) for calculating the physico-chemical parameters from the composition of natural amphiboles is also reported. It gives warnings whenever the input composition is incorrect or diverges from that of the calibration data and includes diagrams for an easy graphical representation of the results.